DO ESG RATINGS DRIVE STOCK PERFORMANCE? AN EMPIRICAL STUDY OF INDONESIAN LISTED FIRMS - Imamah, Nur; Arifin, Layyin Nafisa; Darmawan, Ari; Trinugroho, Irwan; Krissanti, Aurence Dea (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
As Indonesia advances its Green Economy and Sustainable Finance initiatives, Environmental, Social, and Governance (ESG) considerations have become increasingly important in corporate evaluation. The Indonesian Stock Exchange (IDX) now provides publicly accessible ESG ratings that significantly influence investor decisions, while the Financial Services Authority (OJK) actively promotes sustainable finance practices. This study examines the relationship between ESG ratings and financial performance among Indonesian publicly listed companies, specifically investigating whether profitability moderates the impact of ESG ratings on stock price performance. Using a quantitative research design, we analyze data from Indonesian public companies listed on the IDX over a defined period. Multiple regression analysis is employed to examine the relationships between ESG ratings, stock price performance, and profitability measures, including return on assets (ROA). Classical assumption tests ensure the validity of our statistical models. We hypothesize that higher ESG ratings positively influence stock price performance, reflecting growing investor preference for companies with strong sustainability practices. Furthermore, we propose that profitability serves as a moderating variable, with highly profitable companies experiencing stronger positive effects from superior ESG ratings compared to less profitable firms. The findings provide valuable insights for multiple stakeholders. Investors can better understand how ESG factors interact with financial performance in the Indonesian market context. Corporate managers can make informed strategic decisions regarding sustainability investments and their potential market impact. Policymakers can assess the effectiveness of current ESG initiatives and develop enhanced regulatory frameworks. This research contributes to the growing literature on ESG financial materiality in emerging markets.